The Impact of Fair Value Measurement for Bank Assets on Information Asymmetry and the Moderating Effect of Own Credit Risk Gains and Losses - Fontes, Joana C.; Panaretou, Argyro; Peasnell, Kenneth V. (The Accounting Review, 2018)
ABSTRACT We examine whether the use of fair value measurement (FVM) for bank assets reduces information asymmetry among equity investors (bid-ask spread) and how this is affected by the recognition of own credit risk gains and losses (OCR). Our findings show that FVM of assets is associated with noticeably lower information asymmetry, and that this reduction is more than twice as large when banks also recognize OCR. In addition, we find that the bid-ask spread is incrementally lower for banks that provide more detailed narrative disclosures on OCR. The findings also indicate that the effects of asset FVM and OCR recognition on the bid-ask spread do not simply capture the differences in the characteristics of the banks and the quality of their information environments. Data Availability: All data are available from public sources.